Exercise‐induced thoracic outlet syndrome and concomitant osteomyelitis in cervical rib with a possible familial origin: A case report. Issue 4 (22nd April 2022) - Bint I Bilal, Ammara; Gul, Mohammadshah Isam; Ata, Fateen; Ibrahem, Renan E.; Danjuma, Muhammad I.
Abstract: Cervical ribs are rare and usually asymptomatic. Occasionally, they can cause nerve impingements and compressive symptoms. In cervical ribs, osteomyelitis secondary to trauma is unheard of. We report such a case made more interesting by the familial presence of bilateral cervical ribs in two generations, indicating a familial origin. Abstract : Cervical can present with thoracic outlet syndromes. Rarely, cervical ribs may present with osteomyelitis, which can be secondary to internal injury to the adjacent muscles. Additionally, cervical ribs may have a familial origin.